Paparan Pestisida Paraquat Terhadap Kejadian Anemia pada Pekerja Pertanian Padi “X” - Wiwiet Wulandari; Elvi Sunarsih; Vivi Oktari (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Palembang, 2025)
The use of Paraquat pesticides is carried out by sugarcane plantation workers as an effort to control pests and plant diseases. The use of Paraquat pesticides on sugarcane plantation workers can improve the quality and quantity of the harvest produced. Long-term exposure to paraquat pesticides can increase the risk of chronic health disorders. Pesticides contain strong chemicals, if exposed continuously can interfere with the production of red blood cells in the body. Paraquat pesticides that enter the human body can cause poisoning and various health disorders, one of which is anemia. The purpose of this study was to determine the relationship between the use of Personal Protective Equipment (PPE) and the duration of paraquat pesticide spraying with the incidence of anemia in sugarcane plantation workers